Analysis of the Effects of Economic Policy on Car Demand in Indonesia - Moh. Zuhal Zainal (Institute of Computer Science (IOCS), 2021)
This study is aims to analyze and to find out the impact of economy policy for demand for cars in Indonesia. The variables consist of this study such as GDP per kapita, lenght of road, price of BBM, interest rate for credit consumption and demand for cars. This study use the secondary data through Badan Pusat Statistik analyzed by multiple linear regression and Eviews 8 program. The results showed that R Square value of 0.994, which means that 99% of demand for cars is jointly influenced by variables in the model. While the remaining is influenced by other factors outside the model. The partial result shows the GDP per kapita has not affect, lenght of road give a positive affect and significant, price BBM give a positive affect and significant, and interest rate of credit consumption has not affect to demand for cas in Indonesia during the periode of this study